This place has no atmosphere - Danziger, Paula, 1944- (New York : Puffin Books, 2006)
Aurora loves her life on Earth in the twenty-first century, until she learns that her family is moving to the colony on the Moon.
Originally published: Delacorte Press, 1986.
Published by PaperStar Books, 1999.
Keywords: Moving, Household -- Juvenile fiction; Moving, Household -- Fiction; Science fiction; Moon -- Juvenile fiction; Moon -- Fiction; Science fiction